Gastrointestinal thickness, duration, and leak pressure of six intestinal anastomoses in dogs. Issue 7 (22nd July 2020) - Mullen, Kaitlyn M.; Regier, Penny J.; Waln, Monica; Fox‐Alvarez, W. Alexander; Colee, James
Abstract: Objective: To compare leak pressures and construct completion time of six intestinal anastomoses and report normal canine gastrointestinal thickness. Study design: Experimental study. Animals: Grossly normal jejunal segments (n = 140) from 10 fresh canine cadavers. Methods: Gastrointestinal thickness was recorded. Eight‐centimeter cooled canine cadaveric jejunal segments were randomly assigned to a control group (20 segments) and six treatment groups (20 segments/group [10 constructs/group]): (1) handsewn anastomosis (HSA), (2) functional end‐to‐end stapled anastomosis (FEESA)‐blue thoracoabdominal (TA; FEESA‐TAB), (3) FEESA‐green TA (FEESA‐TAG), (4) FEESA TA‐gastrointestinal anastomosis (GIA), (5) FEESA with suture oversew (FEESA‐O), and (6) skin staples (SS). Construct assembly time, initial leak pressure (ILP), maximum intraluminal pressure (MIP), and leakage location were compared. Results: Initial leak pressures (mean ± SD) for control (308.38 ± 115.91 mm Hg), HSA (41.96 ± 15.97), FEESA‐TAB (31.71 ± 15.71), FEESA‐TAG (27.24 ± 14.11), FEESA‐GIA (25.62 ± 11.22), FEESA‐O (31.01 ± 17.38), and SS (44.42 ± 28.88) groups were compared. No difference in ILP ( P  > .24) or MIP ( P  > .17) was detected between treatment groups. Sutured anastomoses took up to 10 times longer to complete ( P = .0025). The stomach, duodenum, jejunum, and ileum mural thicknesses (mean ± SD) were 3.99 ± 0.44 mm, 2.34 ± 0.16, 2.49 ± 0.28, and 2.30 ± 0.31, respectively. Conclusion: The ILP of all anastomoses exceeded maximum intraluminal peristaltic pressures. Stapled anastomoses were faster to complete. Clinical significance: All anastomoses may be considered when performing an intestinal resection and anastomosis, with stapled anastomoses resulting in a shorter surgical time. Canine intestinal thickness may warrant use of a larger staple size.